The hazard of coseismic gaps: the 2021 Fukushima earthquake. Issue 1 (27th May 2021) - Kiser, Eric; Kehoe, Haiyang
SUMMARY: Subduction zones are associated with significant seismic hazards around the world and determining the future locations of large earthquakes within these systems is a perpetual challenge of the Earth sciences. This study presents back-projection results from the 2021 M w 7.1 Fukushima earthquake which show that the rupture area of this event filled a previously identified coseismic gap within the rupture area of the 2011 M w 9.1 Tohoku-oki earthquake. These results, combined with observations of a similar coseismic gap from the 2010 M w 8.8 Maule, Chile earthquake that was subsequently filled by a M w 7.1 aftershock, demonstrate that future assessments of seismic hazards following giant earthquakes should include the identification of coseismic gaps left within main shock rupture areas.